A high-efficient electrochemical synthesis of a low-nuclearity copper-cluster-based metal–organic framework for the size-selective oxidation of alcohols. Issue 18 (27th July 2022) - Huang, Zixuan; Zhang, Lin; Hou, Jiayou; Xu, Tengjiao; Song, Bowen; Bai, Xi; Fu, Hai; Guo, Peipei
Abstract : A copper-cluster-based micropore MOF, namely H-1e, possessing excellent oxidation activity for alcohols (mini-size) to aldehydes with over 99% selectivity and 99% yield, has been obtained by a highly efficient electrochemical synthesis. Abstract : It is highly desirable yet challenging to incorporate open micropores with mass transportation and open active metal sites into metal–organic frameworks (MOFs) for developing novel highly efficient catalysts. Herein, we report a catalyst of low-nuclearity copper-cluster-based micropore MOF, namely H-1e, incorporated with unsaturated Cu(ii ) centres as open active sites obtained via a highly efficient electrochemical synthesis within 20 minutes. The catalyst H-1e shows potential porosity with 1D open functionalized hexagonal channels for size-selective air oxidation as well as high stability. The electrochemically prepared H-1e exhibits excellent catalytic aerobic oxidation activity for the conversion of alcohols (mini-size) to aldehydes with over 99% selectivity and 99% yield under air conditions, showing excellent reusability and stability. The selective catalytic performances are found to be closely dependent on the suitable aperture size of the 1D channels in H-1e, which provided better beds for the oxidation transformations (confirmed by the computational DFT study). In this study, it offers a simple and potential strategy to construct microporous materials with open active metal sites to promote the catalytic efficiency of MOFs by electrochemical synthesis.